Towards a safe and orderly migration: A global migration compact may help combat the myth that migrants are liabilities - Kingsley Ighobor (Africa Renewal, 2019)
In August 2018, French President Emmanuel Macron, German Chancellor Angela Merkel and British Prime Minister Theresa May visited countries in Africa, sparking hope of increased foreign direct investments (FDI) in the continent.